Real world experience with cyclin dependent kinase inhibitors in metastatic breast cancer in India - Anindya Mukherjee; Pankaj Goyal; Rupal Tripathi; Sumit Goyal; Ullas Batra; Vineet Talwar; Varun Goel; Arpit Jain; Shekhar Saha; Sneha Bothra; Chaturbhuj Agrawal; Swati Chugh; et al. (PLoS ONE, 2026)
Background The present study evaluated the real-world experience with cyclin dependent kinase 4/6 inhibitors palbociclib and ribociclib in hormone receptor-positive/ human epidermal growth factor receptor 2-negative (HR + /HER2-) metastatic breast cancer. Method This study was conducted on the HR + /HER2- metastatic breast cancer patients who received palbociclib/ ribociclib in the first line or recurrent setting between January 2021 and January 2023 along with endocrine therapy. Data was retrieved from the Hospital medical records. Results In the patients receiving palbociclib, a better median progression free survival (PFS) was observed in patients with Eastern Cooperative Oncology Group (ECOG) performance status (PS) 1 (27.3 months,p-value <0.0001), de novo disease (17.5 months,p-value 0.0155), first line hormonal therapy (22.5 months,p-value <0.0001) and no prior chemotherapy (20.3 months,p-value 0.0001). Similarly, in the patients receiving ribociclib, a better median PFS was observed in patients with ECOG PS 1 (22.2 months,p-value <0.0001), de novo disease (21.7 months,p-value 0.0042), first-line hormonal therapy (22.5 months,p-value <0.0001) and no prior chemotherapy (21.7 months,p-value <0.0001). On multivariate analysis, ECOG PS, line of hormone therapy and prior chemotherapy showed significance (p-values <0.0001, < 0.0001 & 0.0269, respectively). Conclusion The study shows real-world experience with cyclin dependent kinase 4/6 inhibitors palbociclib and ribociclib in metastatic breast cancer in India.